Conditioned media of pancreatic cancer cells and pancreatic stellate cells induce myeloid-derived suppressor cells differentiation and lymphocytes suppression - Yuen Ping Chong; Evelyn Priya Peter; Feon Jia Ming Lee; Chu Mun Chan; Shereen Chai; Lorni Poh Chou Ling; Eng Lai Tan; Sook Han Ng; Atsushi Masamune; Siti Aisyah Abd Ghafar; Norsharina Ismail; Ket Li Ho (Nature Portfolio, 2024)
Indexed by WOS/Scopus/ERA